2018
DOI: 10.4236/jmmce.2018.64034
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties Characterization of WC-Co-Cr Thermal Spray Coatings

Abstract: WC-Co-Cr coatings are widely employed due to their improved wear resistance and mechanical properties, however, the properties and performance of these coatings are compromised by the processing parameters of each spraying technique. Therefore, this study is aimed to evaluate and determine the effect of the deposition parameters on the properties and microstructural characteristics of WC-Co-Cr coatings using a more economical thermal spray technique. In particular, the influence of flame spray parameters on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…Especially WC-based powders are widely used as they are characterized by a very high hardness compared to most cermets, and addition of, for example, Cr and Co as binding ingredients improves their strength and provides better coatings adhesion. In the case of sprayed coatings from Cr 3 C 2 -NiCr powders, plastic NiCr phase is the matrix, and the reinforcement is hard Cr 3 C 2 particles, which are resistant to abrasion [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Especially WC-based powders are widely used as they are characterized by a very high hardness compared to most cermets, and addition of, for example, Cr and Co as binding ingredients improves their strength and provides better coatings adhesion. In the case of sprayed coatings from Cr 3 C 2 -NiCr powders, plastic NiCr phase is the matrix, and the reinforcement is hard Cr 3 C 2 particles, which are resistant to abrasion [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the hard phase dispersed in the microstructure was a key factor for conferring superior wear resistance despite the presence of the relatively higher pores. 8,13…”
Section: Solid Particle Erosion Behaviormentioning
confidence: 99%
“…WC-Co-based coatings protected the steel substrates from wet and dry abrasion conditions and also observed that finer WC particles were associated with increased wear resistance. [6][7][8][9][10][11] Jonda et al 12 and Mendez-Medrano et al 13 evaluated the microstructure and phase characterization of tungsten carbide and chromium carbide coatings. They noticed that the X-ray diffractometry (XRD) pattern of the coatings indicated the WC and Cr 3 C 2 decarburization phases and disintegration of WC particles occurs, resulting in substantial amounts of W 2 C, W, and Co 3 W 3 C. Schwetzke et al 14 and Matikainen et al 15 investigated the microstructure of WC-based coatings on mild steel substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…WC-10Co-4Cr composite or alloy is widely used for coating applications in aeronautics, mining, construction, and heavy machinery industries [1,2]. In general, WC-Co-Cr based coatings are characterized by having high hardness and high wear, erosion, and corrosion resistance [3,4].…”
Section: Introductionmentioning
confidence: 99%